Follow that bear if you dare! - Freedman, Claire; Edgson, Alison (Intercourse, PA : Good Books, 2008)
Hare and Rabbit bravely venture off on a bear hunt together, carefully following the instructions in Hare's "Best Book of Bear Hunting.".
1.3
K-3
Keywords: Bears -- Juvenile fiction; Hares -- Juvenile fiction; Rabbits -- Juvenile fiction; Bears -- Fiction; Hares -- Fiction; Rabbits -- Fiction; Bears -- Fiction; Rabbits -- Fiction